RELATIONSHIP BETWEEN SOCIAL ANXIETY WITH SELF DISCLOSURE ON GAY IN JAKARTA - Anwar Aly, Amanah; Saputra, Adam; Widiastuti, Mariyana; Adjeng Mariana, R (International Journal of Psychosocial Rehabilitation, 2020)
The negative stigma of society towards gays makes them choose to hide their identity, and even tends to cover their identity by pretending they don’t experience differences in sexual orientation. Even though the gay people themselves need relations and social to be accepted in their environment. Gay people in Jakarta tend to choose to hold back and limit the story because they feel scared rejected. Rejection received by the style resulted in gays unable to express themselves. The purpose of this study was to determine the relationship of social anxiety with self-disclosure and to determine the level of social anxiety and self-disclosure variables. This study is quantitative correlational with a sample of 100 subjects with gay sexual orientation, using non-probability sampling techniques. Social anxiety measuring devices are 24 valid items and reliability 0.841 with social anxiety scale based on La Greca & Lopez’s theory (1998) Self-disclosure measuring devices are 45 valid items and reliability 0.841 with self-disclosure scale based on Devito’s theory (1989). The results of this study indicate there is no relationship between social anxiety with self-disclosure in gays in Jakarta with a sig (p) value of 0.811 and r = 0.024. Or in other words that social anxiety does not affect self-disclosure. The results of this study also produce data that social anxiety accounts only for 0.06% of self-disclosure.